1963
DOI: 10.1128/jb.85.3.707-711.1963
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITION OF THE GROWTH OF AGENTS OF THE PSITTACOSIS GROUP BYd-CYCLOSERINE AND ITS SPECIFIC REVERSAL BYd-ALANINE

Abstract: JULIUS E. OFFICER. Inhibition of the growth of agents of the psittacosis group by D-cycloserine and its specific reversal by D-alanine. J. Bacteriol. 85:707-711. 1963.-D-Cycloserine inhibited multiplication of four members of the psittacosis group in chick embryo yolk sac. D-Alanine reversed each inhibition. In infections with the agent of mouse pneumonitis, the most sensitive member of the psittacosis group tested, D-alanine competitively antagonized the growth inhibition produced bv D-cycloserine. Of a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 13 publications
5
26
0
Order By: Relevance
“…Moulder et al first reported that DCS inhibited the growth of Chlamydia psittaci in chick embryo sacs (Moulder et al, 1963). This study also demonstrated that growth inhibition by DCS could be reversed in the presence of exogenous D-Ala or a racemic mixture of DL-Ala-DL-Ala but not L-Ala or other D-amino acids.…”
Section: Minimal Inhibitory Concentration (Mic) Of Dcs Against C Trasupporting
confidence: 60%
See 2 more Smart Citations
“…Moulder et al first reported that DCS inhibited the growth of Chlamydia psittaci in chick embryo sacs (Moulder et al, 1963). This study also demonstrated that growth inhibition by DCS could be reversed in the presence of exogenous D-Ala or a racemic mixture of DL-Ala-DL-Ala but not L-Ala or other D-amino acids.…”
Section: Minimal Inhibitory Concentration (Mic) Of Dcs Against C Trasupporting
confidence: 60%
“…Although not used clinically, DCS is a substrate analogue of D-Ala that inhibits the function of Ddl proteins. For over 40 years, it has been known that the psittacosis group of Chlamydia is sensitive to DCS (Moulder et al, 1963). Like the psittacosis group, C. trachomatis is also sensitive to DCS (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These gradients were centrifuged at 43,000 x g for 1 h at 4°C in an SW27 rotor. The EB bands, located at the 44/52% Renografin interface, were collected, diluted with 3 volumes of SPG, and then centrifuged at 30,000 x g for 30 min. The EB pellets were washed in SPG to remove residual Renografin.…”
Section: Methodsmentioning
confidence: 99%
“…The exact nature of host-supplied factors and the environmental conditions for typical chlamydial development are unknown. However, deviations from the typical developmental cycle correspond significantly to a variety of alterations in growth conditions, including the presence of antibiotics (3,21,49,59,67,78,119) or host-elaborated factors (10, 66, 107) and deviations in the levels of essential nutrients (1, 25). These conditions generally delay RB maturation, inhibit differentiation to infectious EBs, and are associated with gross morphological alterations of RBs typified by markedly enlarged, atypical chlamydial forms.…”
Section: Altered Chlamydial Developmentmentioning
confidence: 99%